Giant primary omental cyst: an unusual cause of pseudoascites and hydrocele in a child - Hanan Youssif Mohamed (22282399) (2024)
Abdominal lymphangiomas are benign congenital abnormal dilatation and proliferation of lymphatic spaces primarily seen in children. The wide spectrum of symptoms challenges preoperative diagnoses. We present a rare case of a 2-year-old boy presented to pediatrician with massive abdominal distention and left scrotal swelling since the age of 1½ years. Diagnosed and treated as ascites, the patient was referred to pediatric surgery for ascitic tap and hydrocele repair. An abdominal CT scan revealed a giant omental cyst. Laparotomy was performed to excise the cyst extending into left scrotum, and deep left inguinal ring was closed from within. Lymphangioma was histopathologically confirmed. To the best of our knowledge to date, only one case of an omental cystic lymphangioma presenting as bilateral hydroceles without abdominal symptoms has been reported. Nevertheless, this case is unique for the presentation of pseudoascites and a unilateral hydrocele. Other Information Published in: Journal of Surgical Case Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/jscr/rjae774